How should an optimal tax system react to a crisis? Simulation results for Zambia - Dingquan Miao; Ravi Kanbur; Jukka Pirttilä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The COVID-19 pandemic increased public debt and changed the income distribution in many countries. We use a numerical simulation approach to derive optimal nonlinear marginal tax rates for the pre-crisis and crisis periods. We contribute to the literature by examining optimal tax rates numerically for a developing country and by investigating how the tax rates should be changed as a response to a crisis. Our results indicate that the actual extent of redistribution, especially via direct transfers to low-income individuals, should be considerably higher than what the present system offers. Because the crisis increased pre-tax inequality, the tax system should become more redistributive as a response to a crisis. We also demonstrate how a combination of a higher revenue requirement before the crisis and a lower revenue requirement after the crisis increases social welfare.
Keywords: H21; 330; COVID-19 pandemic; optimal income taxation; numerical simulation; welfare analysis